The Impact of Emotional Intelligence and Role of Buddha Philosophy for Stress Management in Private Sector Employees: A Case Study of Birgunj Metropolitan. - Karn, Dipesh Kumar (NPRC Journal of Multidisciplinary Research, 2024)
Background: Emotional intelligence (EI) is often an overlooked topic, particularly in individuals who have a stable financial position and multiple educational degrees but struggle with maintaining healthy relationships. This disconnect leads to heightened stress in personal, family, and social lives. Objective: The objective of this research is to explore how emotional intelligence can aid individuals in understanding their own emotions, fostering empathy, and managing stress, particularly in the context of employees in the private sector of Birgunj metropolis. Methods: The study investigated the levels of stress among private sector employees in Birgunj, focusing on factors such as remuneration, job insecurity, inflation, and post-job life pressures. The research utilized interviews and surveys to assess the emotional well-being and stress factors among these employees. Findings: The research revealed that the most significant stressors were unfair remuneration, job insecurity, high inflation, and a lack of employee benefits. These factors contributed to heightened stress levels, with employees feeling undervalued and overwhelmed by external pressures. Conclusion: Emotional intelligence, along with teachings from Buddhist philosophy, can help individuals manage emotions such as anger, happiness, sadness, and nervousness. Understanding and controlling emotions play a crucial role in improving relationships and reducing stress. Novelty: The novelty of this research lies in its focus on the intersection of emotional intelligence and Buddhist philosophy as tools for stress management in the workplace, particularly in the private sector of Birgunj metropolis.